2010
DOI: 10.1080/09687769.2010.529111
|View full text |Cite
|
Sign up to set email alerts
|

Web-based lecture technologies and learning and teaching: a study of change in four Australian universities

Abstract: The uptake of web-based lecture technologies for recording and delivering live lectures has increased markedly in recent years. Students have responded positively, and for many their use has transformed learning -freeing them up from rigid timetables by providing choice in lecture attendance and supporting learning by extending the lecture experience and enabling them to revisit key concepts and ideas in their own time. Less transformational has been the impact on teaching. Although changing attendance pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 1 publication
5
51
0
Order By: Relevance
“…All of the students in the focus group by Chang (2007) mentioned using lecture capture videos for revisions purposes. Phillips et al (2011) have also noted that access to recorded lectures increased before an assignment was due, and numerous other scholars have observed a peak during exam time (Chen & Lin, 2012;Gorissen, Van Bruggen, & Jochems, 2012;Winer & Cooperstock, 2002). Not all studies confirmed these findings though.…”
Section: The Use Of Lecture Capturesupporting
confidence: 62%
See 4 more Smart Citations
“…All of the students in the focus group by Chang (2007) mentioned using lecture capture videos for revisions purposes. Phillips et al (2011) have also noted that access to recorded lectures increased before an assignment was due, and numerous other scholars have observed a peak during exam time (Chen & Lin, 2012;Gorissen, Van Bruggen, & Jochems, 2012;Winer & Cooperstock, 2002). Not all studies confirmed these findings though.…”
Section: The Use Of Lecture Capturesupporting
confidence: 62%
“…Craig et al (2009) concluded there was "an extremely high uptake by students of the online lectures" (p. 164). Gosper et al (2010) studied lecture capture usage in four Australian universities and found that not only were lecture capture videos being used and well-received by students, they were also being used by students for different reasons, which they note "mirrors" (p. 252) the findings of other research studies.…”
Section: The Use Of Lecture Capturementioning
confidence: 81%
See 3 more Smart Citations